Effect of World Health Organization Based Guidelines on Biomedical Waste Management Knowledge and Practices among Nurses in a Tertiary Care Hospital - Wajiha Hameed, Adnan Yaqoob, Hajra Sarwar, Sadia Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Biomedical waste is the consisting of human tissues or organs, microbiology waste, broken glasses, sharp needles and syringes, drips, cytotoxic drugs, dressings, drips, blood strain items, chemical waste, fluids, urine catheters, and tubes. These wastes are not only harmful to the patients but lead to infections among health care provider and very hazardous for environment. Objectives:To assess the effect of world health organization based guidelines on biomedical waste management Knowledge and practices among nurses in a Tertiary Care Hospital. Methodology: A Quasi-experimental (pre-post) study was carried out at Bahawal Victoria Hospital, Bahawalpur. Overall, 150 nurses were recruited into the study. Data was collected by using an adopted knowledge and practice questionnaire. A total 16 weeks of interventions were organized for the nurses into groups regarding to knowledge and practices of the biomedical waste management. The study was approved by the University of Lahore's Ethical Review Board. Permission was also granted from the hospital administration. Data were analyzed by using SPSS version 24. Results: The mean age of the participants were 33.01 years with a SD of 5.4. The majority (62.7%) of the participants were nursing diploma holders. 66% of the participants were having < 5 years of working experience. Overall, 132(88%) and 100(100%) of participants had poor pre-interventional knowledge and unsatisfactory practices regarding to biomedical waste management. After interventions, 148(99%) and 142(95%) of participants reported good knowledge and safe practices. There was a significant (P= 0.000) enhancement in means of knowledge (2.88 to 12.95) and practices (3.70 to 13.93) scores. Conclusion: The findings of the study reported as poor knowledge and unsafe practices between the nurses regarding to the biomedical waste management. Educational interventions of WHO guidelines proved significant improvement into the knowledge and practices of the nurses regarding to biomedical waste management.